STUDY OF WELL WATER QUALITY FOR AND CONSUMPTION OF RESIDENT IN KENAGARIAN TANAH BAKALI INDERAPURA KABUPATEN PESISIR SELATAN - Nopianti, Hera; Edial, Helfia (Pendidikan Geografi, 2014)
ABSTRACT  The water represent very natural resources for human life. Therefore, water resource need to protect so that still able to in exploiting better by human being and also other life creature exist in world. Clean amount of water required progressively mount along with the increasing of resident growth rate and improvement of society activity in fulfilling requirement of its life.             This research is conducted to analyzed the quality of well water for the consumption of resident and it possibility to be developed to utilize to support amount of water required in Kenagarian Tanah Bakali Inderapura which is progresivelly mount. This research is descriptive research, to analyzed the Quality of Water Well for the consumption of Resident exist in Kenagarian  Tanah Bakali Inderapura quality ofly ( physical, chemical, and biological) quality the of physical quality of colour, temperature and aroma while chemical quality consist of BOD ( Biochemical Oxygen Demand) and COD ( Chemical Oxygen Demand) and to the quality of biology consist of bacterium E. Coli and bacterium of Coli Form. To             Result of research indicate that the quality of physical from well for the consumption of resident fulfill the quality of drinking water , quality of chemistry irrigate well for the consumption of resident for ineligible BOD is quality of drinking water, but from facet of COD fulfill standard which have been specified by PP ( Governmental Regulation) No 82 2001 and if seen from facet of is quality of biologis irrigate well for the consumption of ineligible resident is quality of drinking water which have been specified by Regulation Of Minister for Public Health of RI. No. 492/MENKES/PER/IV/2001